In vitro and in vivo antioxidant activity of soft coffee - Abrahão, Sheila Andrade; Alvarenga, Rosemary Gualberto Fonseca; Sousa, Raimundo Vicente; Lima, Adriene (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to determine the in vivo and in vitro antioxidant activity of soft coffee beverages, before and after roasting. For the analysis of the antioxidant activity, the methods of free radical sequestration (DPPH) and of the chelating activity of Fe2+ ions were used. In vivo tests were performed with diabetic Zucker rats with metabolic syndrome and control Zucker rats. The animals received daily doses of coffee drinks by gavage for 30 days. After treatment, lipid peroxidation was evaluated. Roasted coffee samples had the highest percentage of free radical sequestration. Concentration in both green and roasted coffee samples was similar to that of the Trolox standard. From the roasted samples, medium roast stood out with greater Fe2+ ion chelating activity. Green coffees showed higher quelating power than the roasted ones. The compounds in the extract decreased the lipid peroxidation in the liver and kidney which is common in cases of diabetes and metabolic syndrome. Coffee has an antioxidant activity and protects the liver and kidneys of animals from lipid peroxidation commonly present in type 2 diabetes mellitus and metabolic syndrome.